Pemberdayaan Mandiri Kader Nasyiatul Aisyiyah Tanggap Stunting di Kota Pekalongan: Independent Empowerment of Nasyiatul Aisyiyah Cadres to Respond to Stunting in Pekalongan City - Prafitri, Lia Dwi; Aisyah, Risqi Dewi; Aprilyan, Sherly; Zulfarani, Nelly; Habibah, Naeli (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2024)
Data from Pekalongan City in August 2021 showed a stunting rate of 7.8% under five, which is lower than the national average. Efforts to accelerate stunting handling are carried out by involving Nasyiatul Aisyiyah (NA) as a youth organization in Pekalongan City. NA cadres are targeted to empower independence in handling stunting with education and early detection. However, the obstacles that occur are uneven activities in all branches of NA Pekalongan City and health programs that are limited to screening. Therefore, the independent empowerment of NA cadres in increasing awareness and independence of stunting response is important. The approach method taken is the independent empowerment of NA cadres as subjects and objects in community service activities with the aim of reducing stunting rates and improving student learning experiences as well as the implementation of key performance indicators. This method includes socialization, formation of stunting response NA cadres, provision of education, demonstration examinations, and assistance to provide education and early detection of stunting to the community. This activity received support from various parties so that it can run smoothly and is expected to increase public awareness about the importance of early detection in stunting. Support from various parties is still needed such as the Health Office, Social Office of Population Control and Family Planning, Puskesmas, and the community as an effort to realize zero stunting through independent empowerment of stunting response cadres.